2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--20442
|View full text |Cite
|
Sign up to set email alerts
|

Events that Promote Engineering Students' Intrinsic Motivation to Learn

Abstract: Her research interests include science, technology, engineering, and mathematics (STEM) education; supporting diversity in STEM fields with an emphasis on lesbian, gay, bisexual, transgender, queer, and questioning (LGBTQ) students; and using the Myers-Briggs Type Indicator (MBTI) to improve students' communication skills during group work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
3

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 14 publications
3
57
0
3
Order By: Relevance
“…As examples, Wijnia et al (2011) reported higher learner competence in problem-based learning (PBL) courses compared to lecture-based learning; Liu et al (2009) found high degrees of competence and relatedness in project settings; and Nie and Lau (2010) found higher student self-efficacy and perceived value in courses with constructivist instruction compared to didactic instruction. Trenshaw et al (2014) reported that, compared to exams, design projects have a more positive impact on learner competence, and that relatedness serves as a key factor in promoting internalized motivations in projects. Stolk, Jacobs, et al (2018) illustrated strong positive correlations between competence and autonomy and self-determined motivations in a project-based setting.…”
Section: Motivation and Pedagogymentioning
confidence: 99%
“…As examples, Wijnia et al (2011) reported higher learner competence in problem-based learning (PBL) courses compared to lecture-based learning; Liu et al (2009) found high degrees of competence and relatedness in project settings; and Nie and Lau (2010) found higher student self-efficacy and perceived value in courses with constructivist instruction compared to didactic instruction. Trenshaw et al (2014) reported that, compared to exams, design projects have a more positive impact on learner competence, and that relatedness serves as a key factor in promoting internalized motivations in projects. Stolk, Jacobs, et al (2018) illustrated strong positive correlations between competence and autonomy and self-determined motivations in a project-based setting.…”
Section: Motivation and Pedagogymentioning
confidence: 99%
“…Particularly, [29] argued that it is important whether a game type is appropriate to the learning content and whether the latter is suitable for a game at all, referring to [30] as an illustration. In addition, [31] and [22] advocate that the effectiveness of applying gamification to enhance the level of motivation for studying depends largely on whether the game elements support certain psychological needs of students, which is consistent with the postulates of the self-determination theory. On top of that, [32] emphasizes the worth of game thinking for applying gamification in an educational context.…”
Section: Discussionmentioning
confidence: 68%
“…We report how constructs shifted using coded qualitative data in a descriptive narrative, going construct-by-construct. This methodological process, including how we defined constructs of SDT and how we coded data by SDT constructs, is aligned to other studies using SDT to explore aspects of motivation in teaching and learning contexts (e.g., Hite et al, 2019 ; Jacobi, 2018 ; Trenshaw et al, 2016 ; Virkkula, 2020 ).…”
Section: Methodsmentioning
confidence: 99%